Pharmacokinetic/pharmacodynamic issues for optimizing treatment with beta-lactams of Gram-negative infections in critically ill orthotopic liver transplant recipients: a comprehensive review - Gatti, Milo; Pea, Federico (Frontiers in Antibiotics, 2024)
Orthotopic liver transplant (OLT) represents the standard of care for managing patients affected by end-stage and life-threatening liver diseases. Although a significant improvement in surgical techniques, immunosuppressant regimens, and prompt identification of early post-transplant complications resulted in better clinical outcome and survival in OLT recipients, the occurrence of early bacterial infections still represents a remarkable cause of morbidity and mortality. In this scenario, beta-lactams are the most frequent antimicrobials used in critical OLT recipients. The aim of this narrative review was to provide a comprehensive overview of the pathophysiological issues potentially affecting the pharmacokinetics of beta-lactams and to identify potential strategies for maximizing the likelihood of attaining adequate pharmacokinetic/pharmacodynamic (PK/PD) targets of beta-lactams in critically ill OLT recipients. A literature search was carried out on PubMed-MEDLINE database (until 31st March 2024) in order to retrieve clinical trials, real-world observational evidence, and/or case series/reports evaluating the PK/PD of traditional and novel beta-lactams in settings potentially involving critically ill OLT recipients. Retrieved evidence were categorized according to the concepts of the so-called “antimicrobial therapy puzzle”, specifically assessing a) beta-lactam PK/PD features, with specific regard to aggressive PK/PD target attainment; b) site of infection, with specific regard to beta-lactam penetration in the lung, ascitic fluid, and bile; and c) pathophysiological alterations, focusing mainly on those specifically associated with OLT. Overall, several research gaps still exist in assessing the PK behavior of beta-lactams in critical OLT recipients. The impact of specific OLT-associated pathophysiological alterations on the attainment of optimal PK/PD targets may represent an important field in which further studies are warranted. Assessing the relationship between aggressive beta-lactam PK/PD target attainment and clinical outcome in critical OLT recipients will represent a major challenge in the next future.